Sinergitas Guru Agama, Orang Tua, dan Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran PAI di SMA NW Narmada - Ahmad Baihaqi; Alkusaeri Alkusaeri; Saparudin Saparudin (MANAZHIM, 2023)
The objectives of this study are to analyze 1) the role of religious teachers, parents, and school principals; 2) the forms of synergy among religious teachers, parents, and school principals. The research method employed is descriptive qualitative research. Data were gathered through interviews, field notes, and documentation. Data collection techniques included interviews, observations, and documentation. The research findings present the following 1) the roles of religious teachers include: a) educator; b) administrator; c) supervisor; d) innovator. The roles of parents encompass a) educator and caregiver; b) mentor and supporter; c) facilitator and motivator. The roles of school principals involve a) educator; b) manager; c) supervisor; d) innovator. 2) the applied forms of synergy consist of a) involving parents in program development; b) fostering intensive communication; c) initiating introductions with parents; d) conducting regular meetings with parents.